The role of biodiversity in Southeast Asian tropical forest restoration - Veryard, R (2023)
Tropical forests in Sabah, Malaysian Borneo, are threatened by land use change and continued overexploitation. Active restoration of dipterocarp-dominated forests is used to increase the restoration value of these landscapes, and knowledge of the ecological mechanisms that promote tropical forest functioning is critical to realising this goal..